ANÃLISIS DE LAS ACTIVIDADES EXTRAESCOLARES EN FUNCIÃ“N DE LA VARIABLE GÉNERO EN EL ALUMNADO DE PRIMARIA DE LA PROVINCIA DE GRANADA - Calero, Inmaculada Argüelles; Sánchez, Antonio Campos; Núñez, Juan Antonio López (European Scientific Journal, ESJ, 2015)
This study has been done to carry out a theoretical basis about the extracurricular activities that primary students do in Granada, looking at both: those activities related to sports and those related to school (cultural and artistic). It has been based on the variable of gender and we have made a desing of a descriptive research investigation based on both techniques: the interview and the questionnaire.